Screening a mouse liver gene expression compendium identifies modulators of the aryl hydrocarbon receptor (AhR). (2nd October 2015) - Oshida, Keiyu; Vasani, Naresh; Thomas, Russell S.; Applegate, Dawn; Gonzalez, Frank J.; Aleksunes, Lauren M.; Klaassen, Curtis D.; Corton, J. Christopher
Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that mediates the biological and toxic effects of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD), dioxin-like compounds (DLC) as well as some drugs and endogenous tryptophan metabolites. Short-term activation of AhR can lead to hepatocellular steatosis, and chronic activation can lead to liver cancer in mice and rats. Analytical approaches were developed to identify biosets in a genomic database in which AhR activity was altered. A set of 63 genes was identified (the AhR gene expression biomarker) that was dependent on AhR for regulation after exposure to TCDD or benzo[a]pyrene and includes the known AhR targets Cyp1a1 and Cyp1b1 . A fold-change rank-based test (Running Fisher's test; p -value ≤10 −4 ) was used to evaluate the similarity between the AhR biomarker and a test set of 37 and 41 biosets positive or negative, respectively for AhR activation. The test resulted in a balanced accuracy of 95%. The rank-based test was used to identify factors that activate or suppress AhR in an annotated mouse liver/mouse primary hepatocyte gene expression database of ∼1850 comparisons. In addition to the expected activation of AhR by TCDD and DLC, AhR was activated by AP20189 and phenformin. AhR was suppressed by phenobarbital and 1, 4-Bis[2-(3, 5-dichloropyridyloxy)] benzene (TCPOBOP) in a constitutive activated receptor (CAR)-dependent manner and pregnenolone-16α-carbonitrile in a pregnane X receptor (PXR)-dependent manner. Inactivation of individual genes in nullizygous models led to AhR activation ( Pxr, Ghrhr, Taf10 ) or suppression ( Ahr, Ilst6st, Hnf1a ). This study describes a novel screening strategy for identifying factors in mouse liver that perturb AhR in a gene expression compendium.